Jeffrey Moore’s The Memory Artists:: Synaesthesia, Science, and the Art of Memory - Fortin, Marc (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
Jeffrey Moore’s The Memory Artists (2004) represents a recent turn in contemporary Canadian literature involving texts that investigate the implications, ethics, histories, and epistemological power structures of science, scientific theories, and the linguistic and philosophical interplay between literature and science. Attending to the philosophical tradition of Henri Bergson, Silvan Tomkins, and Jean-Paul Sartre highlights the ways in which the representation of biological conditions such as synaesthesia and hypermnesia, as well as Alzheimer’s and amnesia, inform The Memory Artists – how the chemical makeup of individuals produces different ways of knowing the world and forces us to question what separates human knowledge from the material body in which it arises. In doing so, the novel reconstitutes the traditional boundaries between memory and matter, science and art, and the fictional and factual into a sliding scale of degrees of difference.